Arrhythmia susceptibility in a rat model of acute atrial dilation. (August 2020) - Scardigli, M.; Cannazzaro, S.; Coppini, R.; Crocini, C.; Yan, P.; Loew, L.M.; Sartiani, L.; Cerbai, E.; Pavone, F.S.; Sacconi, L.; Ferrantini, C.
Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia, associated with an increased risk of stroke and heart failure. Acute AF occurs in response to sudden increases of atrial hemodynamic load, leading to atrial stretch. The mechanisms of stretch-induced AF were investigated in large mammals with controversial results. We optimized an approach to monitor rat atrial electrical activity using a red-shifted voltage sensitive dye (VSD). The methodology includes cauterization of the main ventricular coronary arteries, allowing improved atrial staining by the VSD and appropriate atrial perfusion for long experiments. Next, we developed a rat model of acute biatrial dilation (ABD) through the insertion of latex balloons into both atria, which could be inflated with controlled volumes. A chronic model of atrial dilation (spontaneous hypertensive rats; SHR) was used for comparison. ABD was performed on atria from healthy Wistar-Kyoto (WKY) rats (WKY-ABD). The atria were characterized in terms of arrhythmias susceptibility, action potential duration and conduction velocity. The occurrence of arrhythmias in WKY-ABD was significantly higher compared to non-dilated WKY atria. In WKY-ABD we found a reduction of conduction velocity, similar to that observed in SHR atria, while action potential duration was unchanged. Low-dose caffeine was used to introduce a drop of CV in WKY atria (WKY-caff), quantitatively similar to the one observed after ABD, but no increased arrhythmia susceptibility was observed with caffeine only. In conclusion, CV decrease is not sufficient to promote arrhythmias; enlargement of atrial surface is essential to create a substrate for acute reentry-based arrhythmias.